2023
DOI: 10.1111/1753-0407.13389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neprilysin and neprilysin inhibitors on glucose homeostasis: Controversial points and a promising arena

Abstract: Neprilysin (NEP) is a transmembrane zinc‐dependent metalloproteinase that inactivates various peptide hormones including glucagon‐like peptide 1 (GLP‐1). NEP inhibitors may be effective in the management of type 2 diabetes mellitus (T2DM) by increasing the circulating level of GLP‐1. However, acute‐effect NEP inhibitors may lead to detrimental effects by increasing blood glucose independent of GLP‐1. These findings suggest a controversial point regarding the potential role of NEP inhibitors on glucose homeosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Systemic expression of TSHRs suggests the role of TSH in different cardiometabolic processes and inflammatory reactions regardless of the thyroid gland. It has been reported that high TSH level is associated with an increased risk of cardiovascular diseases by reducing of insulin sensitivity and lipid metabolism [55,56]. A cross-sectional study conducted by Wang et al [57] showed that TSH affects lipid metabolism through THsdependent and THs-independent mechanisms causing hypercholesterolemia.…”
Section: Thyroid-stimulating Hormonementioning
confidence: 99%
“…Systemic expression of TSHRs suggests the role of TSH in different cardiometabolic processes and inflammatory reactions regardless of the thyroid gland. It has been reported that high TSH level is associated with an increased risk of cardiovascular diseases by reducing of insulin sensitivity and lipid metabolism [55,56]. A cross-sectional study conducted by Wang et al [57] showed that TSH affects lipid metabolism through THsdependent and THs-independent mechanisms causing hypercholesterolemia.…”
Section: Thyroid-stimulating Hormonementioning
confidence: 99%
“… 85 It has been shown that overactivation of Cdk5 induces aberrant phosphorylation of neurofilaments; tau protein and amyloid precursor protein (APP) result in the formation of NFTs and associated mitochondrial dysfunction and neuronal apoptosis. 86 During neuronal stress both p39 and p35 are cleaved by calpain to p25 and p29; result in formation of Cdk5/p25 complex which has long and potent effect by 10‐fold than p35 in the activation of APP. 87 Therefore, Cdk5 and its activators are augmented and correlated with Aβ and NFTs in AD (Figure 3 ).…”
Section: Role Of Cdk5 In Neurodegenerative Diseasesmentioning
confidence: 99%
“…In the context of insulin resistance, earlier investigations have shown a connection between the Renin‐Angiotensin‐Aldosterone system (RAAS) and ER stress. [ 187 ] Ang‐II increases the ER stress in adipose tissue. ACE2 improves mitochondrial and ER function to reduce intramuscular fat.…”
Section: Nrf2 In Covid‐19mentioning
confidence: 99%